ANTIHYPERTENSIVE POTENTIAL OF FLAVONOID-CONTAINING MEDICINAL PLANTS: A NARRATIVE REVIEW - Kadek Diah Lestari Kencana; Ni Made Pitri Susanti (Journal Pharmaceutical Science and Application, 2026)
Background: Hypertension is a prevalent chronic disease and a major cause of cardiovascular morbidity and mortality. Flavonoid-containing medicinal plants have attracted attention as potential natural antihypertensive agents. Objective: This review summarizes the antihypertensive potential of flavonoid-containing medicinal plants and their underlying mechanisms. Methods: A narrative literature review was conducted using PubMed and Google Scholar. Original articles published between 2015 and 2024 were selected based on predefined inclusion and exclusion criteria. Eligible studies investigated flavonoid-containing medicinal plants using in silico, in vitro, ex vivo, or animal models. Ten studies were included for qualitative analysis. Results: The reviewed plants contained flavonoids, including quercetin, kaempferol, luteolin, and rutin, which exhibited antihypertensive potential through ACE inhibition, enhanced nitric oxide bioavailability, and antioxidant activity. Evidence varied across molecular docking, laboratory, and animal studies. Conclusion: Flavonoid-containing medicinal plants are promising preclinical antihypertensive candidates; however, further pharmacological and clinical studies are required to confirm their efficacy and safety. Keywords: Flavonoids; Herbal Medicines; Hypertension; Medicinal Plants; Phytopharmaceuticals